(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Gas turbine is one of most important turbo machines in the industrial scenario. It has a greater scope in power generation, aviation, refineries and small industries. The main theme of the paper to design, drafting a turbine blade. The using 3D softwaresolid works by using the Coordinate measuring machine point data available. The two turbine blade models are designed namely turbine blade with hole and turbine blade without hole. In order to determine the deformation and maximum shear stress values for the blades, static analysis is carried out using fluent software. Then modal analysis of the blade is carried out in order to find the mode shapes and natural frequencies. The results obtained from this work will a very useful in the field of gas turbine design